Effect of Pregelatinization and Retrogradation on Some Physicochemical Changes of Wheat-Potato Starches - Nesimi Aktaş; Kamil Emre Gerçekaslan (Journal of Agricultural Sciences)
The freezable (FW) and unfreezable water (UFW) contents of wheat and potato starches and their physically modified forms [pregelatinized (PGS) and retrograded (RS)] were analyzed by Differential Scanning Calorimetry (DSC) at various hydration levels (25, 35, 45, 55, 65, 75 and 85%). In all the starch samples, the UFW content increased with increasing hydration level. Potato starch samples (native, pregelatinized and retrograded) had higher UFW contents than wheat starch samples at all hydration levels. Similarly, with the increase of hydration level in all starch samples, onset (To), peak (Tp) and endset (Te) temperatures of the peaks also increased. It was obtained that physical modifications in starches had significant effects (P<0.05) on water absorption index (WAI) and water solubility index (WSI) of starch samples. The highest WAI (10.51) and WSI (2.31) values were determined in pregelatinized potato starches. Rapid Visco Analyzer (RVA) profiles revealed that physically modified starches had higher viscosity values than native starches. The results clearly showed that pregelatinization and retrogradation had positive effects on the physicochemical properties studied.